Analisis Prinsip-Prinsip Penggembalaan Berdasarkan 1 Petrus 5:1-3 dan Implementasinya Masa Kini - Talan, Yesri Esau; Bilo, Dyulius Thomas; Tomusu, Anita Yumbu (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
Herding is the duty and responsibility of a shepherd. God calls a shepherd to perform a noble task. But in the present context the essence of grazing is incorrectly implemented. Therefore, it is important to understand the principles of herding based on 1 Peter 5:1-3 and to be used as an example in the practice of herding. The methods used are qualitative methods with descriptive analysis. 1 Peter 5:1-3 becomes the material of analysis coupled with other sources of refrence. The results obtained show that the main principles in herding are, herding voluntarily in the sense of not demanding reward, shepherding with devotion or faithfulness in service and being exemplary in words, deeds and attitudes. These principles need to be applied in the pastoring of present-day contexts. The goal is to lead the congregation to grow in faith.